Method of the relevance degree estimation of the text answer in computer training systems - Badorina, L.N. (Proceedings of National Aviation University (archive), 2007)
The article proposes the method of a trainee’s text answer analysis on the task of the open type allowing establishing conformity with terms of a subject domain.